2009
DOI: 10.1242/jeb.033183
|View full text |Cite
|
Sign up to set email alerts
|

The cost of assuming the life history of a host: acoustic startle in the parasitoid fly Ormia ochracea

Abstract: SUMMARYIn the obligatory reproductive dependence of a parasite on its host, the parasite must trade the benefit of 'outsourcing' functions like reproduction for the risk of assuming hazards associated with the host. In the present study, we report behavioral adaptations of a parasitic fly, Ormia ochracea, that resemble those of its cricket hosts. Ormia females home in on the male cricket's songs and deposit larvae, which burrow into the cricket, feed and emerge to pupate. Because male crickets call at night, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 59 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…These evasive responses are usually graded, meaning that the responses change in a quantitative or qualitative manner with increasing sound amplitude. Almost all other insects with bat-evasive behaviours also show this pattern of graded response, changing from small alterations in flight direction or speed to drastic, last-ditch behaviours as sound amplitude at their ears increases (green lacewings: Miller and Olesen, 1979;crickets: Nolen and Hoy, 1986;mantids: Yager et al, 1990;beetles: Forrest et al, 1995;some katydids: Schulze and Schul, 2001; tachinid flies: Rosen et al, 2009). This is a highly adaptive pattern for bat avoidance.…”
Section: Bat-avoidance Behaviour In Moths and Other Insectsmentioning
confidence: 98%
See 1 more Smart Citation
“…These evasive responses are usually graded, meaning that the responses change in a quantitative or qualitative manner with increasing sound amplitude. Almost all other insects with bat-evasive behaviours also show this pattern of graded response, changing from small alterations in flight direction or speed to drastic, last-ditch behaviours as sound amplitude at their ears increases (green lacewings: Miller and Olesen, 1979;crickets: Nolen and Hoy, 1986;mantids: Yager et al, 1990;beetles: Forrest et al, 1995;some katydids: Schulze and Schul, 2001; tachinid flies: Rosen et al, 2009). This is a highly adaptive pattern for bat avoidance.…”
Section: Bat-avoidance Behaviour In Moths and Other Insectsmentioning
confidence: 98%
“…Fossil evidence shows that hearing evolved in orthopterans for intraspecific communication before the appearance of bats (Plotnick and Smith, 2012). Tachinid flies that listen for the calling songs of their cricket hosts also had ears before bats evolved (Rosen et al, 2009). For both of these groups, hearing was co-opted for bat detection in addition to still performing its original function.…”
Section: Anti-predator Adaptations the Evolutionary Origins Of Bat-dementioning
confidence: 99%
“…In principle, our approach could also be applied to quantify signal preferences during flight. Flying phonotaxis has been studied in O. ochracea using a tethered flight paradigm (Rosen et al, 2009). Similarly to crickets, flies adopt steering maneuvers toward stimuli with the temporal pattern and frequency content of cricket calling songs (∼4.5 kHz), but steer away from stimuli with ultrasonic frequencies (>20 kHz) that are characteristic of bat sonar (Wyttenbach et al, 1996;Rosen et al, 2009).…”
Section: Advantages and Limitations Of The Phonotaxis Performance Indexmentioning
confidence: 99%
“…Flying phonotaxis has been studied in O. ochracea using a tethered flight paradigm (Rosen et al, 2009). Similarly to crickets, flies adopt steering maneuvers toward stimuli with the temporal pattern and frequency content of cricket calling songs (∼4.5 kHz), but steer away from stimuli with ultrasonic frequencies (>20 kHz) that are characteristic of bat sonar (Wyttenbach et al, 1996;Rosen et al, 2009). Developing an index to quantify performance in flying phonotaxis would likely involve measuring response latencies and the magnitude of steering maneuvers to (or away from) the source location.…”
Section: Advantages and Limitations Of The Phonotaxis Performance Indexmentioning
confidence: 99%
“…Ormia is also sensitive to sounds in the ultrasonic range and until recently no function had been attributed to this second area of best hearing (Robert et al, 1992). Rosen, et al (2009) found Ormia to elicit an acoustic startle response to ultrasonic stimuli, much like that of their orthopteran hosts. Both the parasitoid fly and its cricket host use hearing for a function other than predator avoidance, yet due to their nocturnal lifestyle and exposure to predators, possess hearing structures that secondarily have evolved to function in predator detection.…”
Section: Insect Ears: Single or Multi-functionalmentioning
confidence: 99%